2020
DOI: 10.1210/clinem/dgaa629
|View full text |Cite
|
Sign up to set email alerts
|

Follistatin-like 1 as a Novel Adipomyokine Related to Insulin Resistance and Physical Activity

Abstract: Background and Aims FSTL-1 is considered to be an adipokine or myokine that could be a potential regulator of metabolism. Our purpose is to investigate the relationship between circulating FSTL-1 levels and insulin resistance (IR) in type 2 diabetes mellitus (T2DM) and to identify the regulatory factors. Methods FSTL-1 expression in C57BL/6J and db/db mice was examined by qRT-PCR and Western blots. Serum FSTL-1 levels were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…This result corroborates data obtained by human analysis that have shown how circulating FSTL-1 levels in obese and diabetic subjects were higher than in lean subjects. Moreover, Xu X et al have demonstrated that FSTL-1 protein expression increased dramatically in response to physical activity in healthy subjects [194]. These results confirm study performed by Kon et al that have proved that acute endurance exercise may stimulate the secretion of FSTL1 and apelin [195].…”
Section: Follistatin-like 1: Biological Rolesupporting
confidence: 70%
“…This result corroborates data obtained by human analysis that have shown how circulating FSTL-1 levels in obese and diabetic subjects were higher than in lean subjects. Moreover, Xu X et al have demonstrated that FSTL-1 protein expression increased dramatically in response to physical activity in healthy subjects [194]. These results confirm study performed by Kon et al that have proved that acute endurance exercise may stimulate the secretion of FSTL1 and apelin [195].…”
Section: Follistatin-like 1: Biological Rolesupporting
confidence: 70%
“…The physical examination included body weight, blood pressure (BP), waist circumference (WC), and body fat content (Fat %). Biochemical parameters included total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), free fatty acid (FFA), HbA1c, FBG, 2-hour postprandial blood glucose (2h-BG), fasting insulin (FIns), and 2-hour postprandial insulin (2h- INS), as previously reported ( Xu et al, 2020 ).…”
Section: Research Population and Methodsmentioning
confidence: 99%
“…Physical activity was found to significantly increase the circulating FSTL-1 concentration in young, healthy subjects. Likewise, FSTL-1 protein expression in AT rose dramatically in response to physical activity [ 42 ].…”
Section: Metabotrophic Factors As Therapeutic Targets In Drug Discoverymentioning
confidence: 99%